2004
DOI: 10.1111/j.1365-2249.2004.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-16 expression and release in bullous pemphigoid

Abstract: SUMMARY Cutaneous infiltration of activated CD4+ T cells and eosinophils is an early event in blister formation during bullous pemphigoid (BP), suggesting that the trafficking of circulating leucocytes through the sites of inflammation, their activation and cytokine release is crucial in the pathogenesis of the disease. IL-16 is a major chemotactic factor able to recruit CD4 + cells in the skin during inflammation and to induce the expression of functional high-affinity interleukin (IL)-2 receptors, thus contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
1
30
0
3
Order By: Relevance
“…This observation would tend to favor the ''British Hypothesis'' that asthma and COPD (in particular, emphysema) are distinct diagnoses as opposed to the Dutch hypothesis, which postulates that the two diseases are related through a continuum of airway inflammation (Barnes, 2006). Although the role that IL-16 might play in emphysema and COPD is unknown, one possibility is that it is ( Lard et al, 2002;Lee et al, 1998), rheumatoid arthritis (RA) (Blaschke et al, 2001;Lard et al, 2004); bullous pemphigoid (Frezzolini et al, 2004), diabetes (Meagher et al, 2010), and preeclampsia (Gu et al, 2008). In a mouse model of rheumatoid arthritis, IL-16 attenuates joint inflammation (Klimiuk et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This observation would tend to favor the ''British Hypothesis'' that asthma and COPD (in particular, emphysema) are distinct diagnoses as opposed to the Dutch hypothesis, which postulates that the two diseases are related through a continuum of airway inflammation (Barnes, 2006). Although the role that IL-16 might play in emphysema and COPD is unknown, one possibility is that it is ( Lard et al, 2002;Lee et al, 1998), rheumatoid arthritis (RA) (Blaschke et al, 2001;Lard et al, 2004); bullous pemphigoid (Frezzolini et al, 2004), diabetes (Meagher et al, 2010), and preeclampsia (Gu et al, 2008). In a mouse model of rheumatoid arthritis, IL-16 attenuates joint inflammation (Klimiuk et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A variety of activated inflammatory cells, particularly autoreactive T cells and eosinophils, participate in blister formation by producing and releasing a number of cytokines and soluble factors involved in amplifying and maintaining tissue damage. [3][4][5][6][7] Early cutaneous infiltration by eosinophils seems to be a crucial event in the development of bullous lesions, 8 but the pathophysiological role of these cells is still unclear. It is known that eosinophils are the major intravascular source of tissue factor (TF), an initiator of the extrinsic coagulation pathway, 9 and it has recently been demonstrated that TF (and therefore the extrinsic pathway of coagulation leading to thrombin generation) is involved in chronic urticaria 10,11 and related to increased vasopermeability.…”
Section: Discussionmentioning
confidence: 99%
“…Various inflammatory cells, notably activated CD4+ T cells showing the functional features of T-helper 2 lymphocytes, 5,15 infiltrate BP lesions, but a prominent infiltrating cell is the eosinophil. 8 Eosinophils are found scattered throughout the upper dermal infiltrate or aggregated at the edge of the dermal-epidermal separation.…”
Section: Discussionmentioning
confidence: 99%
“…Different cell types, including T and B lymphocytes and a variety of innate immune cells, eosinophils, mast cells, airway epithelial cells, dendritic cells and keratinocytes, are able to synthesize IL-16 [14,15,16,17,18,19,20]. In T cells, IL-16 is generated as a precursor molecule, pro-IL-16, which is cleaved by caspase-3, yielding the secreted, biologically active cytokine [14,21].…”
Section: Discussionmentioning
confidence: 99%